Implementasi Peraturan Bupati Kabupaten Aceh Jaya Nomor 21 Tahun 2011 Tentang Penataan Pertambangan Emas Rakyat - Aminah Aminah; Effendi Hasan; Ubaidullah Ubaidullah (Jurnal Public Policy, 2021)
The development of gold for the people of Aceh Jaya district has had a wide impact on the community around the mining area. Therefore, the Aceh Jaya district government has enacted regent regulation no 21 of 2011 regarding the arrangement of community mining, but the policy implementation has not been optimal. The research was peeled off using implementation models from Smith as well as Van Metter and Van Horn. This study aims to analyze the implementation of Aceh Jaya government policies in structuring community gold mining in Gunong Ujeun village, Krueng Sabee sub-district, Aceh Jaya district. This research uses a qualitative method, namely by interviewing informants. The results of the study illustrate that the implementation of the policy or regional regulation of Aceh Jaya district number 21 of 2011 has not been running optimally. This can be seen from the number of miners who do not know the existence of the regulations set by the government. In addition, the lack of monitoring on the part of the government has also resulted in community gold mining in Gunong Ujeun being continuously mining illegally by the community, either individually or through established cooperatives.